2020
DOI: 10.1002/art.41122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cumulative Inflammation, Cardiac Risk Factors, and Medication Exposure on Coronary Atherosclerosis Progression in Rheumatoid Arthritis

Abstract: Objective To explore incidence and progression of coronary atherosclerosis and identify determinants in patients with rheumatoid arthritis (RA). We specifically evaluated the impact of inflammation, cardiac risk factors, duration of medication exposure, and their interactions on coronary plaque progression. Methods One hundred one participants with baseline coronary computed tomography angiography findings underwent follow‐up assessment a mean ± SD of 83 ± 3.6 months after baseline. Plaque burden was reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 41 publications
5
65
3
Order By: Relevance
“…Emerging information supports similar effects for non-TNFi biologics (13,14). We recently reported that longer biologic DMARD exposure was associated with a lower likelihood of increase in noncalcified plaque burden in RA (6). Biologic DMARD use also predicted decreases in noncalcified plaque and necrotic core burden in patients with psoriasis (15).…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Emerging information supports similar effects for non-TNFi biologics (13,14). We recently reported that longer biologic DMARD exposure was associated with a lower likelihood of increase in noncalcified plaque burden in RA (6). Biologic DMARD use also predicted decreases in noncalcified plaque and necrotic core burden in patients with psoriasis (15).…”
Section: Introductionmentioning
confidence: 63%
“…We previously reported that RA disease activity was associated with greater coronary plaque burden and vulnerability (5). Cumulative inflammation also predicted coronary plaque progression in RA (6). Lastly, subclinical coronary plaque burden was associated with mid-term CVD events in RA above and beyond traditional risk factors or the Framingham-D'Agostino score of cardiovascular risk (7,8).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…According to recently published data, coronary artery calci cation increases with higher total prednisone dose, by contrast methotrexate and other csDMARDs do not in uence coronary plaque progression [33]. Furthermore, DMARD and TNF-α antagonists are associated with reduced risk of myocardial infarction, stroke and cardiovascular death [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…The traditional cardiovascular risk scores underestimate the real cardiovascular risk in RA [29][30][31]. CCS is better in CV risk strati cation in RA than combinations of the traditional CV risk factors [32,33]. Here we investigated the baseline and follow-up CCS of RA patients and studied its progression over time.…”
Section: Introductionmentioning
confidence: 99%